The subjective career success of women: The role of personal resources - Koekemoer, Eileen; Olckers, Chantal; Schaap, Pieter (Frontiers in Psychology, 2023)
Introduction Research on women’s career success has been the subject of extensive investigations, emphasizing the barriers they encounter in their careers. However, far less attention has been given to the personal resources that promote women’s career success. The purpose of our study was to provide more conclusive evidence regarding the role that personal resources such as resilience and grit can play in the relationship between women’s person-environment fit and the perceptions of their career success. Underpinned by the Job Demands Resources and social cognitive theory, our study aims to investigate whether resilience and grit could either explain how person-environment fit translates into feelings of subjective career success or could strengthen this relationship. Method A cross-sectional online survey research design was used, and a convenience sample of 408 female employees was obtained. Relationships were explored through structural equation modelling. Results When controlling for age, the findings of this study revealed significantly positive relationships between the constructs, with person-environment fit, resilience, and grit, explaining a large portion of the variance in subjective career success. Although our data supported the mediating role of grit and resilience in the person-environment fit and subjective career success relationship, the moderating effects of grit and resilience could not be established. Discussion These findings illustrate both grit and resilience as mechanisms that indirectly affect the person-environment fit and subjective career success relationship of women. However, our findings indicate that resilience and grit cannot be considered mechanisms that would buffer against poor person-environment fit’s effect on their career success perceptions. Firstly, our study advances our understanding of the roles personal resources such as resilience and grit play in women’s career success as ways to overcome obstacles and workplace barriers. Secondly, using the motivational process of the Job Demands Resources Framework as theoretical background, we contribute by shedding light on how personal resources (resilience and grit) can be considered underlying factors influencing the person-environment fit and career success relationship for women. If women experience good person-environment fit, there is a greater opportunity for developing resilience and grit and, consequently, subjective career success.